English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

y= -x²+9x-3 and the line y=3x
I got the anwser 3+/- √9, but how do I apply this to the equations?

Show/explain please.

2007-08-29 13:28:24 · 1 answers · asked by Anonymous in Science & Mathematics Mathematics

1 answers

How did you get this answer?
y = 3x = -x²+9x-3 therefore x² - 6x + 3 = 0
x = [6+-√(36 - 12)]/2 = 3+-√6

2007-08-29 15:04:51 · answer #1 · answered by Hahaha 7 · 0 0

fedest.com, questions and answers